2005
DOI: 10.1136/bjo.2005.068171
|View full text |Cite
|
Sign up to set email alerts
|

The achiasmia spectrum: congenitally reduced chiasmal decussation

Abstract: Aim: To describe the clinical spectrum of achiasmia, a congenital disorder of reduced relative decussation at the optic chiasm. Methods: A retrospective case note and patient review of nine children (four boys). Achiasmia was defined by the combination of a characteristic asymmetry of the monocular visual evoked potential (VEP) response to flash and neuroimaging showing reduced chiasmal size. Results: Three of the children had an associated skull base encephalocele with agenesis of the corpus callosum. In two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…The ophthalmological findings in the present study relating to these children with achiasmia and albinism are in agreement with previous studies [12,17]. In these four children with achiasmia, their ophthalmological findings are presented in detail [47].…”
Section: Ocular Findings and Mri Characteristicssupporting
confidence: 93%
See 3 more Smart Citations
“…The ophthalmological findings in the present study relating to these children with achiasmia and albinism are in agreement with previous studies [12,17]. In these four children with achiasmia, their ophthalmological findings are presented in detail [47].…”
Section: Ocular Findings and Mri Characteristicssupporting
confidence: 93%
“…Therefore, the lack of uniformity in VEP asymmetries shown previously has also been found in the present study. In the majority of previous studies, ipsilateral asymmetry was observed with flash and pattern onset stimulation [3][4][5][6][7], while crossed asymmetry and crossed contralateral positivity have also been associated with achiasmia [8][9][10][11][12]36]. In the present study, the ipsilateral asymmetry defines the absent optic-nervefibre decussation at the chiasm for both of the eyes.…”
Section: Ocular Findings and Mri Characteristicsmentioning
confidence: 46%
See 2 more Smart Citations
“…They may also have developmental delay and optic disc anomalies. 72 Three types have been suggested: 72 1. Type A: reduced decussation, with basically normal appearing optic nerves on clinical examination.…”
Section: Achiasmiamentioning
confidence: 99%